2006
DOI: 10.1111/j.1365-2745.2006.01124.x
|View full text |Cite
|
Sign up to set email alerts
|

Root competition: beyond resource depletion

Abstract: Summary1 Root competition is defined as a reduction in the availability of a soil resource to roots that is caused by other roots. Resource availability to competitors can be affected through resource depletion (scramble competition) and by mechanisms that inhibit access of other roots to resources (contest competition, such as allelopathy). 2 It has been proposed that soil heterogeneity can cause size-asymmetric root competition. Support for this hypothesis is limited and contradictory, possibly because resou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
430
3
10

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 492 publications
(472 citation statements)
references
References 173 publications
12
430
3
10
Order By: Relevance
“…Competition for space seems unlikely due 387 While we believe that the most likely source of the effect of S. plicata on M. 398 squamiger survival in the field was competition, we must also consider other potential 399 explanations. Allelopathic effects of invasive species on natives have been found in 400 some studies (Schenk 2006;Figueredo et al 2007), and in our study the interaction of 401 the two species might induce the production of waterborne allelopathic metabolites in 402 the introduced species that could reduce both survival and growth of the native. An 403 alternative mechanism for the negative effect of the invasive on the native species in 404 the field is that there are indirect effects via a third organism.…”
Section: Experiments 2: Does the Presence Of Recruits Affect Settlemenmentioning
confidence: 67%
“…Competition for space seems unlikely due 387 While we believe that the most likely source of the effect of S. plicata on M. 398 squamiger survival in the field was competition, we must also consider other potential 399 explanations. Allelopathic effects of invasive species on natives have been found in 400 some studies (Schenk 2006;Figueredo et al 2007), and in our study the interaction of 401 the two species might induce the production of waterborne allelopathic metabolites in 402 the introduced species that could reduce both survival and growth of the native. An 403 alternative mechanism for the negative effect of the invasive on the native species in 404 the field is that there are indirect effects via a third organism.…”
Section: Experiments 2: Does the Presence Of Recruits Affect Settlemenmentioning
confidence: 67%
“…Spatial localization of interactions can also reward greed, selfish behavior, and spite. For example, trees evolve strategies to shade out neighbors (61), or to interfere with neighbors' roots, through mechanisms that would be too costly if their effects were diffused over large areas (62)(63)(64); indeed, it has been suggested that this can lead to a potential tragedy of the commons (63,65). Similarly, plants and microbial organisms produce allelochemics that poison neighbors (66), and selection for these traits depends critically on the fact that the allelochemics will not be diffused over broad areas but will remain close enough to poison the most intense competitors.…”
Section: Prosociality and Spitementioning
confidence: 99%
“…Essa redução foi devido à competição com o milho pelos fatores do crescimento. Abaixo da superfície do solo, as plantas daninhas influenciariam o comportamento do milho, alterando a disponibilidade de nutrientes (Lehoczky & Reisinger, 2003;Kumar et al, 2005) e de água e/ou inibindo o acesso das raízes de milho a esses recursos, por alelopatia (Schenk, 2006). A deficiência d'água, causada pela competição entre raízes, induziria o fechamento dos estômatos, reduzindo a fotossíntese (Silva et al, 2004), e, consequentemente, reduziria também o crescimento de caules, folhas e espigas.…”
Section: Resultsunclassified